PENGARUH MOTIVASI DAN KOMPETENSI PEDAGOGIKTERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL (Studi Kasus pada Guru SMK se-Kecamatan Gunem Kabupaten Rembang) - Sa’dunnaim, 1352020028; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to analyse, experimentally, the relationships between motivation and competencies to teacher performance with school commitments as mediating. Participants compriseed 114 teacher from SMK N in the whole district Gunem (SMK NÂ and SMKÂ Gunem). Data were collected using a questionnaire, after which the data were processed using SPSS 17. Test instruments used are validity and reliability . While ui model used is the coefficient of determination and test FÂ . Test this hypothesis using regression analysis. Result of research analysis express that motivation and competence has positive influence and significant toorganizational commitment, motivation hasnât influence and significant to teacher performance, competence has positive influence and significant to teacher performance, organizational commitment hasnât Â positive influence and significant to teacher performance. Key Words:Â Â Â Â motivation, competencies, teacher performance and organisasion commitmen.